ZONASI LAHAN BERPOTENSI UNTUK BUDIDAYA TANAMAN TEH (CAMELLIA SINENSIS L. KUNTZE) DI SUB DAS PASUI HULU DAS SADDANG - Juanda, Muh Faisal (UNIVERSITAS NEGERI MAKASSAR, 2019)
ABSTRACTThis research aims to know actual land suitability potential for Tea (Camellia Sinensis L. Kuntze) in Pasui Sub watershed, Saddang upstream watershed. The method of this research is random stratified sampling on 58 land units with take 9 samples. From the research summarizes suitability class are suit enough (S2) spread on 6 land units width it is 70,91 ha. Marginal suit (S3) spread on 47 land units width it is 13376,14 ha and not suit (N) spreads on 5 land units width it is 61,85 ha. Conclusions from above that potential to grow tea crop in Pasui sub watershed, Saddang upstream watershed are three class of suitability, Suit enough (S2), Marginal Suit (S3), and Not Suit (N). Most Heavy limiting factor are temperature, nutritions retention in case base saturation and erosion hazards in case slopes.